Euro Area Policies : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper for euro area policies analyzes the product market regulation and benefits of wage moderation. The paper identifies structural shifts in the relationship between wages and unemployment rates-a 'wage curve'-in 20 industrial countries. It reviews euro area and cross-country developments in labor costs and their bivariate relationship with unemployment rates and business GDP. The paper also examines aspects of the European Central Bank's monetary analysis, within the context of their overall two-pillar policy framework, and issues surrounding its use.